2010
DOI: 10.1093/ndt/gfq530
|View full text |Cite
|
Sign up to set email alerts
|

National survey of the current provision of specialist palliative care services for patients with end-stage renal disease

Abstract: The majority of SPC services accept ESRD patients, but limited numbers are referred. Respondents indicated that this barrier could be addressed by closer collaboration and better communication and education between renal and SPC services. Other initiatives to enable delivery of SPC to increased numbers of ESRD patients include the use of specific referral and clinical care guidelines and expansion of joint MDT meetings and out-patient clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…However, recent data (26) demonstrate that specialist palliative care services accepted more referrals of patients with ESRD. Our survey has shown that all units now work with specialist palliative care service for CKM patients approaching the end of life, and 79% of units worked with palliative care services from local hospices.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data (26) demonstrate that specialist palliative care services accepted more referrals of patients with ESRD. Our survey has shown that all units now work with specialist palliative care service for CKM patients approaching the end of life, and 79% of units worked with palliative care services from local hospices.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, only 13.5% of the 115 239 dialysis patients who died in a 2-year period used a hospice 64 97. In the UK, there remains some confusion about when dialysis can be considered an active treatment and when it can be considered ‘palliative’ 55 62–65 98. Increasing involvement of primary and palliative care services is helping to address this 42 43 65 98.…”
Section: Delivery Of Care At the End Of Life And Current Controversiesmentioning
confidence: 99%
“…Renal disease is included in the Gold Standards Framework in the United Kingdom [13], again helping the medical team to identify patients at risk of deterioration, initiate care planning and provide support for patients and their carers. However, access for patients with advanced CKD to specialist palliative care services is varied [14] and complicated by decisions around dialysis continuation [15]. …”
Section: Introductionmentioning
confidence: 99%